Ergogenic aids used by ultra-marathon runners - Gwilliams, Michael (Department of Health and Rehabilitation Sciences, 2015)
Background: Athletes of all levels and abilities utilise ergogenic aids to enhance sporting performance. However, the extent of ergogenic aid use within the ultra-marathon running community in unknown and there is little available literature documenting characteristics of use among ultra-marathon runners. Aims and Objectives: The aim of this study is to describe the use of ergogenic aids in ultra-marathon runners. The specific objectives of the study were to: a) To obtain information on the use of ergogenic aids in ultra- marathon runners, with regard to the type of ergogenic aids used, and the pattern of use during training and competition; b) To determine ultra- marathon runner’s perceived benefits of the ergogenic aids; c) To determine the factors influencing the intake strategies of ergogenic aids; d) To explore the factors that may predict the use of ergogenic aids, such as age, gender level of competitiveness, training and competition history. Methods: This study had a descriptive correlational study design. Participants included male and female ultra- marathon runners between 25 and 65 years of age. Participants who did not give informed consent and who failed to meet the defined classifications of being an ultra-marathon runner and medical screening criteria were excluded from the study. Participants were recruited through electronic correspondence, running clubs and running-specific media platforms. A self-developed questionnaire was designed to obtain information on ergogenic aid use in ultra-marathon runners during training and competition, as well as to determine the runners’ pattern of use and their perceived effect of ergogenic aids. The questionnaire was available in English and Afrikaans, and explored both legal and illegal ergogenic aid use. A panel of experts reviewed and validated the questionnaire. The online questionnaire was anonymous; with all referring uniform resource locators (URLs) and internet protocol (IP) addresses of respondents hidden to ensure anonymity. Results: The final sample was comprised of 266 respondents (n=179 males; n=87 females). The mean age of participants was 44 ± 10. The mean number of ergogenic aids used per participant was 5 ± 2. Dietary practice (47%) was the most common ergogenic intervention, followed by supplementary aids (45%), and pharmacological aids (18%). No participants reported the use of illegal/banned ergogenic aids. The highest self-reported ergogenic aid used was s ports drinks (n = 213; 80%) followed by vitamins (n = 181; 68 %) and carbo-loading (n = 165; 62%). Participants tended to use ergogenic aid s predominantly during competition and less so during training. Seventy-nine percent of participants believe d that their chosen ergogenic aid improve d their performance, while 9% did not think their performance was improved, and 9% were uncertain. The most frequently perceived benefits of ergogenic aids were ‘delayed fatigue’ and ‘providing an energy boost ’. Self-experimentation /personal experience, fellow runners and books/magazines were the highest ranked factors influencing intake strategies of the participants chosen aids. Runners who had more than ten years of ultra-marathon running experience were approximately 50% more likely to consume sports drinks. Females were about two and a half times more likely to utilize vitamins as an ergogenic aid. However, evidence from the general population suggests that females have a significantly higher daily intake of vitamins compared to males; therefore this finding might simply reflect daily supplement use and not be specific to ultra-marathon runners. The use of vitamins was also dependant on the number of ultra-marathons performed; participants completing more than five ultra-marathons were almost twice as likely to use vitamins as those completing less than five ultra-marathons. Recreational runners were approximately one third less likely to undertake the dietary practice of carbo-loading than competitive runners. The number of marathons and the number of ultra-marathons completed conversely affected the use of increased protein. This study was unable to identify any descriptive, race or training characteristics that influenced the use of caffeine, medication, gels or electrolytes as ergogenic aids. Conclusion: The findings of this study demonstrated that the prevalence of use of legal ergogenic aids is high and often used simultaneously. This study was unable to identify the prevalence of use of illegal ergogenic aids. However, the inappropriate and potentially unsafe use for many legal ergogenic aids was identified. Participants also reported false performance beliefs, potentially indicating poor knowledge or understanding of the effects of ergogenic aids. A major challenge is the strong influence of personal experience and information from fellow runners on the choice of ergogenic aids. Runners are accessing information through social networking, interactions and possibly social media, rather than scientific resources. Educational initiatives, with a focus on peer-led education, are essential to encourage the safe and effective use of ergogenic aids. This study highlights the importance of collective responsibility of the running community, including regulators, administrators, health care professionals, coaching and support staff, and journalists and authors of books and magazines to ensure that runners are informed about the safe and correct use of legal ergogenic aids.